Interdisciplinarity and Sustainability Challenges - Buarque, Cristovam; Ferreira, Leila da Costa; Jacobi, Pedro Roberto; Sobral, Maria do Carmo; Sampaio, Carlos Alberto Cioce; Fernandes, Valdir (Sustainability in Debate, 2014)
Debate SeD 9